Three-dimensional carbon nanotube modified graphite felt as well as preparation method and application thereof

By growing carbon nanotubes on graphite felt and forming a two-dimensional phthalocyanine structure, the problem of insufficient electrocatalytic activity of the graphite felt electrode was solved, the energy and voltage efficiency of the vanadium battery was improved, and the stability and life of the battery were increased.

CN120767345AActive Publication Date: 2025-10-10HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511283099.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-09
Publication Date
2025-10-10
Estimated Expiration
2045-09-09

AI Technical Summary

Technical Problem

Existing graphite felt used as an electrode material for vanadium batteries has a small specific surface area and insufficient electrocatalytic activity, which limits the improvement of the energy efficiency of vanadium batteries.

Method used

The graphite felt is immersed in a nickel dispersion and subjected to hydrothermal and heat treatments to grow carbon nanotubes and form three-dimensional carbon nanotube-modified graphite felt, thereby enhancing the conductivity and specific surface area. A two-dimensional phthalocyanine is formed by a nitrile source and a nickel salt to provide catalytic active sites.

Benefits of technology

The energy and voltage efficiency of the all-vanadium redox flow battery are improved, the structural stability of the carbon nanotubes is enhanced, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120767345A_ABST
    Figure CN120767345A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of all-vanadium redox flow battery electrodes, and discloses a three-dimensional carbon nanotube modified graphite felt and a preparation method and application thereof.The preparation method includes the following steps that carbon nanotubes are subjected to vapor deposition on the graphite felt twice, phthalocyanine is loaded on the graphite felt through solvothermal, then metal nickel is removed through cleaning, and the three-dimensional carbon nanotube modified graphite felt is obtained; the conductivity can be effectively improved by loading the carbon nanotubes on the graphite felt, and the three-dimensional structure can effectively increase the catalytic active sites of the graphite felt, so that the energy efficiency and the voltage efficiency of the all-vanadium redox flow battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of all-vanadium redox flow battery electrodes, and in particular to a three-dimensional carbon nanotube-modified graphite felt and a preparation method and application thereof. Background Art

[0002] Graphite felt is widely used in all-vanadium redox flow batteries due to its low price, good chemical stability, and high mechanical strength. However, as an electrode material for vanadium batteries, it suffers from a small specific surface area and insufficient electrocatalytic activity, which has become a bottleneck limiting further improvements in vanadium battery energy efficiency. Carbon nanotubes, with their excellent chemical stability, electrical conductivity, and large specific surface area, hold promise for further enhancing the electrocatalytic activity of graphite felt electrodes. In light of this, a three-dimensional carbon nanotube-modified graphite felt, its preparation method, and its application are proposed. Summary of the Invention

[0003] The purpose of the present invention is to provide a three-dimensional carbon nanotube modified graphite felt and a preparation method and application thereof, so as to overcome the deficiencies in the prior art.

[0004] A first aspect of the present invention provides a method for preparing a three-dimensional carbon nanotube-modified graphite felt, comprising the following steps: Step S1: immersing graphite felt in a nickel dispersion to react and obtain carbon nanotube-modified graphite felt; Step S2: mixing and stirring the nickel salt, nitrile source, and DMF uniformly, adding the carbon nanotube-modified graphite felt to perform hydrothermal treatment to obtain hydrothermally treated graphite felt; Step S3: heat-treating the hydrothermally treated graphite felt to grow carbon nanotubes, thereby obtaining a precursor graphite felt; Step S4: washing the precursor graphite felt with dilute hydrochloric acid and freeze-drying the mixture to obtain three-dimensional carbon nanotube-modified graphite felt.

[0005] In a preferred embodiment, in step S1: The nickel powder in the nickel dispersion has a particle size of 100-200 nm and a nickel powder concentration of 0.1 mol / L.

[0006] In a preferred embodiment, in step S1: The graphite felt was immersed in a nickel dispersion for reaction and then heat-treated to grow carbon nanotubes. Specifically, argon gas was first introduced to raise the temperature to 750-850°C and kept warm for 0.5h. Then, acetylene gas was introduced at a flow rate of 80-120sccm and kept warm for 0.5-3h. Finally, argon gas was introduced to cool down.

[0007] The carbon nanotubes deposited by heat treatment can effectively improve the conductivity and specific surface area of ​​graphite felt, thereby improving the energy efficiency and voltage efficiency of all-vanadium liquid flow batteries.

[0008] In a preferred embodiment, in step S2: The nickel salt is selected from at least one of nickel chloride and nickel nitrate; The nitrile source is selected from at least one of 4-hydroxyphthalonitrile, 4,5-dihydroxyphthalonitrile, 4-aminophthalonitrile, and 4-chlorophthalonitrile.

[0009] In a preferred embodiment, in step S2: The weight ratio of the nickel salt, the nitrile source and the DMF is 1:2:50.

[0010] In a preferred embodiment, in step S2: The temperature of the hydrothermal treatment is 140-180° C., and the time is 8-12 hours.

[0011] Two-dimensional phthalocyanine is formed by hydrothermal treatment of nitrile source and nickel salt. On the one hand, a large number of pores are generated after subsequent pyrolysis and hydrochloric acid treatment, providing more catalytic active sites for graphite felt. On the other hand, carbon nanotubes can be further fixed on the carbon fibers of graphite felt, thereby improving the structural stability of graphite felt. At the same time, it can also act as an efficient catalyst in the generation process of the outermost carbon nanotubes.

[0012] In a preferred embodiment, in step S3: The method for growing carbon nanotubes by heat treatment is as follows: first, argon gas is introduced to raise the temperature to 750-850°C, and the temperature is kept at this temperature for 0.5 hours. Then, a mixed gas consisting of hydrogen and argon with a volume ratio of 5:95 is introduced, and the temperature is kept at this temperature for 0.5 hours. Then, acetylene gas is introduced at a flow rate of 80-120 sccm, and the temperature is kept at this temperature for 0.5-1.5 hours. Finally, argon gas is introduced to cool the mixture.

[0013] The formation step of the outermost carbon nanotubes is additionally added with mixed gas, so that nickel oxide is reduced to nickel element in situ, which can increase the generation amount and bonding strength of the outermost carbon nanotubes.

[0014] In a preferred embodiment, in step S4: The freeze-drying temperature is -60°C and the time is 15 hours.

[0015] The second aspect of the present invention provides a three-dimensional carbon nanotube-modified graphite felt, which is prepared by the preparation method described above.

[0016] The third aspect of the present invention provides an application of a three-dimensional carbon nanotube-modified graphite felt. The three-dimensional carbon nanotube-modified graphite felt prepared by the above-mentioned preparation method or the three-dimensional carbon nanotube-modified graphite felt described above is applied to an all-vanadium redox flow battery.

[0017] The beneficial effects of the present invention include at least: The vapor-deposited carbon nanotubes in the present invention can effectively improve the conductivity and specific surface area of ​​the graphite felt, thereby improving the energy efficiency and voltage efficiency of the all-vanadium redox flow battery; The three-dimensional carbon nanotube structure constructed by vapor deposition, solvothermal deposition, vapor deposition, and metal removal can provide more active sites for vanadium ion reactions; The nitrile source and nickel salt form a two-dimensional phthalocyanine, which produces a large number of pores after thermal decomposition and hydrochloric acid treatment, providing more catalytic active sites. The nitrile source contains a large amount of nitrogen element, and the doping of nitrogen element can improve the electrochemical performance of the battery. The three-dimensional carbon nanotube structure constructed by the present invention can effectively improve the structural stability of the carbon nanotubes loaded on the graphite felt and increase the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a scanning electron microscope image of the three-dimensional carbon nanotube-modified graphite felt prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0019] The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention, its application, or use. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without inventive effort are intended to fall within the scope of protection of the present invention.

[0020] Example 1: Using the following technical solutions Step S1: ultrasonically dispersing 0.01 mol of nickel powder in 100 g of deionized water to form a 0.1 mol / L nickel powder solution, impregnating the graphite felt, and drying; Step S2: placing the dried graphite felt in a tube furnace, introducing argon gas, heating to 800° C. and holding the temperature for 0.5 h, then introducing acetylene gas at a flow rate of 100 sccm and holding the temperature for 1 h, and finally introducing argon gas to cool the temperature to obtain carbon nanotube-modified graphite felt; Step S3: dissolving 1 part by mass of nickel chloride and 2 parts by mass of 4-hydroxyphthalonitrile in 50 parts by mass of DMF, mixing and stirring the mixture evenly, adding carbon nanotube-modified graphite felt, and hydrothermally treating the mixture at 140° C. for 8 h; Step S4: The hydrothermally treated graphite felt is cleaned and dried, placed in a tube furnace, and heated to 800°C for 0.5 h by introducing argon gas, then heated for 0.5 h by introducing a 5:95 mixture of hydrogen and argon gas, and finally heated for 0.5 h by introducing acetylene gas, and then cooled again by introducing argon gas to obtain a precursor graphite felt; Step S5: The precursor graphite felt is placed in a 3 mol / L hydrochloric acid solution to wash and remove the metallic nickel, and then freeze-dried to obtain a three-dimensional carbon nanotube-modified graphite felt.

[0021] pass Figure 1 Scanning electron microscopy of three-dimensional carbon nanotube-modified graphite felt shows that the surface of the graphite felt is wrapped with carbon nanotubes and the carbon nanotubes have a three-dimensional structure.

[0022] Example 2: Using the following technical solutions Step S1: ultrasonically dispersing 0.01 mol of nickel powder in 100 g of deionized water to form a 0.1 mol / L nickel powder solution, impregnating the graphite felt, and drying; Step S2: placing the dried graphite felt in a tube furnace, introducing argon gas, heating to 750° C. and holding the temperature for 0.5 h, then introducing acetylene gas at a flow rate of 80 sccm and holding the temperature for 0.5 h, and finally introducing argon gas to cool the temperature to obtain carbon nanotube-modified graphite felt; Step S3: dissolving 1 part by mass of nickel nitrate and 2 parts by mass of 4,5-dihydroxyphthalonitrile in 50 parts by mass of DMF, mixing and stirring the mixture evenly, adding carbon nanotube-modified graphite felt, and hydrothermally treating the mixture at 180° C. for 12 h; Step S4: The hydrothermally treated graphite felt is cleaned and dried, placed in a tube furnace, and heated to 750°C by introducing argon gas and kept at this temperature for 0.5 h. A mixture of hydrogen and argon in a ratio of 5:95 is then introduced and kept at this temperature for 0.5 h. Finally, acetylene gas is introduced and kept at this temperature for 0.25 h. Argon gas is introduced again to cool the mixture to obtain a precursor graphite felt. Step S5: placing the precursor graphite felt in a 3 mol / L hydrochloric acid solution to remove the metallic nickel, and freeze-drying at -60°C for 15 hours to obtain a three-dimensional carbon nanotube-modified graphite felt.

[0023] Example 3: Using the following technical solution Step S1: ultrasonically dispersing 0.01 mol of nickel powder in 100 g of deionized water to form a 0.1 mol / L nickel powder solution, impregnating the graphite felt, and drying; Step S2: placing the dried graphite felt in a tube furnace, introducing argon gas, heating to 850° C. and holding the temperature for 0.5 h, then introducing acetylene gas at a flow rate of 100 sccm and holding the temperature for 3 h, and finally introducing argon gas to cool the temperature to obtain carbon nanotube-modified graphite felt; Step S3: dissolving 1 part by mass of nickel chloride and 2 parts by mass of 4-aminophthalonitrile in 50 parts by mass of DMF, mixing and stirring the mixture evenly, adding carbon nanotube-modified graphite felt, and hydrothermally treating the mixture at 160° C. for 10 h; Step S4: The hydrothermally treated graphite felt is cleaned and dried, placed in a tube furnace, introduced with argon gas, heated to 850°C and kept warm for 0.5 h, then introduced with a 5:95 mixture of hydrogen and argon gas and kept warm for 0.5 h, finally introduced with acetylene gas and kept warm for 1.5 h, and then introduced with argon gas again to cool down to obtain a precursor graphite felt; Step S5: placing the precursor graphite felt in a 3 mol / L hydrochloric acid solution to remove the metallic nickel, and freeze-drying at -60°C for 15 hours to obtain a three-dimensional carbon nanotube-modified graphite felt.

[0024] Example 4: Using the following technical solutions Step S1: ultrasonically dispersing 0.01 mol of nickel powder in 100 g of deionized water to form a 0.1 mol / L nickel powder solution, impregnating the graphite felt, and drying; Step S2: placing the dried graphite felt in a tube furnace, introducing argon gas, heating to 800° C. and holding the temperature for 0.5 h, then introducing acetylene gas at a flow rate of 100 sccm and holding the temperature for 2 h, and finally introducing argon gas to cool the temperature to obtain carbon nanotube-modified graphite felt; Step S3: dissolving 1 part by mass of nickel nitrate and 2 parts by mass of 4-chlorophthalonitrile in 50 parts by mass of DMF, mixing and stirring the mixture evenly, adding carbon nanotube-modified graphite felt, and hydrothermally treating the mixture at 180° C. for 8 h; Step S4: The hydrothermally treated graphite felt is cleaned and dried, placed in a tube furnace, and heated to 800°C for 0.5 h by introducing argon gas, followed by introducing a 5:95 mixture of hydrogen and argon gas for 0.5 h, and finally introducing acetylene gas for 1 h, followed by introducing argon gas again to cool the furnace to obtain a precursor graphite felt; Step S5: placing the precursor graphite felt in a 3 mol / L hydrochloric acid solution to remove the metallic nickel, and freeze-drying at -60°C for 15 hours to obtain a three-dimensional carbon nanotube-modified graphite felt.

[0025] Comparative Example 1: Using the following technical solutions The preparation process is consistent with that of Example 1, except that no nickel salt is involved in step S3.

[0026] Comparative Example 2: Using the following technical solutions The preparation process is consistent with that of Example 1, except that no nitrile source is involved in step S3.

[0027] Comparative Example 3: Using the following technical solutions The preparation process is the same as that of Example 1, except that step S5 is not performed.

[0028] Comparative Example 4: Using the following technical solutions The preparation process is the same as that of Example 1, except that the mixed gas in step S4 is not replaced with argon.

[0029] 1. Battery test: The graphite felts prepared in the examples and comparative examples were assembled into a battery stack, and a charge-discharge cycle test was performed under the same operating conditions to record the coulombic efficiency, energy efficiency, and voltage efficiency of the battery stack.

[0030] 2. Powder loss test: The graphite felt prepared in the examples and comparative examples was cut into pieces of 3*3 cm, placed in deionized water, and shaken at 30°C for 3 hours. Afterwards, it was rinsed with deionized water and dried. The mass change of the graphite felt before and after was measured.

[0031] The test results are shown in Table 1: Table 1 Performance test results of graphite felt of examples and comparative examples

[0032] The above test results show that compared with Comparative Example 1, Examples 1-4 have higher voltage efficiency and energy efficiency, indicating that although the nitrile source is loaded on the graphite felt, there is no participation of the nickel salt, and the catalytic active sites provided are limited; compared with Comparative Example 2, Examples 1-4 have higher voltage efficiency and energy efficiency, indicating that although the nickel salt is loaded on the graphite felt, there is no participation of the nitrile source, and the catalytic active sites provided are limited; compared with Comparative Example 3, Examples 1-4 have higher voltage efficiency and energy efficiency, indicating that the three-dimensional carbon nanotube structure constructed by vapor deposition, solvent thermal, vapor deposition, and metal removal can provide more active sites for vanadium ion reaction. Compared with Comparative Examples 1-4, Examples 1-4 have better voltage efficiency after 200 cycles and smaller graphite felt mass change, indicating that the three-dimensional carbon nanotube structure constructed by the present invention can effectively improve the stability of the carbon nanotube structure loaded on the graphite felt and improve the cycle life of the battery.

[0033] 3. Carbon nanotube production and structural strength test Take 12 pieces of graphite felt of the same specifications and test their initial mass. Then, take 3 pieces of graphite felt from each of the three graphite felts and treat them using the preparation methods of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 4. After the treatment, weigh the graphite felt and calculate the average mass change M1 before and after the treatment. Finally, place the graphite felt in deionized water and shake it at 30°C for 3 hours. After the treatment, rinse with deionized water, dry it, and weigh the average mass change M2 before and after the treatment. The results are shown in Table 2: Table 2 Changes in graphite felt mass in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 4

[0034] Table 2 shows that Example 1 has a greater M1 than Comparative Example 4, indicating that the use of a mixed gas in the step of forming the outermost carbon nanotube layer can reduce nickel oxide to elemental nickel in situ, thereby increasing the production of the outermost carbon nanotube layer. Furthermore, the M2 result shows that Example 1 has a smaller mass loss than Comparative Example 4, indicating that the carbon nanotubes in Example 1 have a greater bonding strength. Example 1 has greater M1 and M2 than Comparative Examples 1 and 2, indicating that the phthalocyanine in the intermediate layer can not only increase the active sites of the graphite felt during vanadium battery operation, but also act as a highly efficient catalyst in the production of the outermost carbon nanotube layer, and can also fix the inner carbon nanotubes, improving structural stability.

[0035] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing three-dimensional carbon nanotube-modified graphite felt, characterized in that: The following steps are involved: Step S1: immersing graphite felt in a nickel dispersion to react and obtain carbon nanotube-modified graphite felt; Step S2: mixing and stirring the nickel salt, nitrile source, and DMF uniformly, adding the carbon nanotube-modified graphite felt to perform hydrothermal treatment to obtain hydrothermally treated graphite felt; Step S3: heat-treating the hydrothermally treated graphite felt to grow carbon nanotubes, thereby obtaining a precursor graphite felt; Step S4: washing the precursor graphite felt with dilute hydrochloric acid and freeze-drying the mixture to obtain three-dimensional carbon nanotube-modified graphite felt.

2. The preparation method according to claim 1, wherein In the step S1: The nickel powder in the nickel dispersion has a particle size of 100-200 nm and a nickel powder concentration of 0.1 mol / L.

3. The preparation method according to claim 1, wherein In the step S1: The graphite felt was immersed in a nickel dispersion for reaction and then heat-treated to grow carbon nanotubes. Specifically, argon gas was first introduced to raise the temperature to 750-850°C and kept warm for 0.5h. Then, acetylene gas was introduced at a flow rate of 80-120sccm and kept warm for 0.5-3h. Finally, argon gas was introduced to cool down.

4. The preparation method according to claim 1, wherein In the step S2: The nickel salt is selected from at least one of nickel chloride and nickel nitrate; The nitrile source is selected from at least one of 4-hydroxyphthalonitrile, 4,5-dihydroxyphthalonitrile, 4-aminophthalonitrile, and 4-chlorophthalonitrile.

5. The preparation method according to claim 1, wherein In the step S2: The weight ratio of the nickel salt, the nitrile source and the DMF is 1:2:

50.

6. The preparation method according to claim 1, wherein In the step S2: The temperature of the hydrothermal treatment is 140-180° C., and the time is 8-12 hours.

7. The preparation method according to claim 1, wherein In the step S3: The method for growing carbon nanotubes by heat treatment is as follows: first, argon gas is introduced to raise the temperature to 750-850°C, and the temperature is kept at this temperature for 0.5 hours. Then, a mixed gas consisting of hydrogen and argon with a volume ratio of 5:95 is introduced, and the temperature is kept at this temperature for 0.5 hours. Then, acetylene gas is introduced at a flow rate of 80-120 sccm, and the temperature is kept at this temperature for 0.5-1.5 hours. Finally, argon gas is introduced to cool the mixture.

8. The preparation method according to claim 1, wherein In the step S4: The freeze-drying temperature is -60°C and the time is 15 hours.

9. A three-dimensional carbon nanotube modified graphite felt, characterized in that: The three-dimensional carbon nanotube-modified graphite felt is prepared by the preparation method according to any one of claims 1 to 8.

10. An application of three-dimensional carbon nanotube modified graphite felt, characterized in that: The three-dimensional carbon nanotube-modified graphite felt prepared by the preparation method according to any one of claims 1 to 8 or the three-dimensional carbon nanotube-modified graphite felt according to claim 9 is used in an all-vanadium redox flow battery.

Citation Information

Patent Citations

  • A construction method of functional graphite felt and its application in vanadium battery

    CN109216706A

  • Preparation method and application of aggregated bimetallic phthalocyanine molecule alloy catalyst

    CN118531429A

  • Modified graphite felt, preparation method thereof and flow battery

    CN118867286A

  • Process of mono temperature area resistance furnace pyrolysis for growing and purifying carbon nanotube

    CN1765736A

  • 3D graphene / carbon nanotube / inorganic oxide structure, fabrication method of the structure, and lithium ion battery including the structure

    KR1020180066615A